CLINICAL EFFICACY OF COMBINATION THERAPY WITH PERINDOPRIL AND INDAPAMIDE IN PATIENTS WITH MILD AND MODERATE ARTERIAL HYPERTENSION - G. J. Abdullayeva; A. B. Khalikova; G. A. Khamidullaeva; R. D. Kurbanov (Евразийский Кардиологический Журнал)
Aim: to study hypotensive and organo-protective efficacy of cornbination therapy with perindopril and indanarnide in patients with rnild and rnoderate arterial hypertension. Material and methods. According to the protocol in the study included 23 patients with I-II grade of arterial hypertension (ESC/ ESH 2013), of both genders. All patients took the cornbination preparation Arnra forte (GMP, Georgia), containing 4 тд of perindopril and 1.25 rrig of indaparnide. At the stage before the treatrnent and 12 weeks of therapy was rneasured an office blood pressure by Korotkov's rnethod and carried out arnbulatory blood pressure rnonitoring (ABPM) ("BR-102 plus Recorder" (SCHILLER, Switzerland)). Antirernodeling efficacy was assessed by the dynarnics of cardiac echo geornetry and ultrasound (US) of vessels pararneters. Also was evaluated the clinical tolerance and rnetabolic effects of the drug. The pararneters of central hernodynarnics and vascular stiffness were rneasured by applanation tonornetry. Results are presented as M±SD. Results of research. 12-week cornbination therapy with perindopril and indaparnide is characterized by high antihypertensive efficacy, with a decrease in rnean blood pressure to 18%, and achievernent the target level of blood pressure in 100% patients with rnild and rnoderate arterial hypertension. According to the ABPM showed a significant decrease of average daily SBP and DBP, as well as a significant decrease in the speed of rnorning SBP surge. Thus it was not iriarked episodes of hypotension at night. Reliable antirernodeling efficacy of perindopril and indaparnide is expressed in reducing LVMI, reducing of EDD and reliably reducing the thickness of IMC against the background of 12-week treatrnent. 12-week cornbination therapy with perindopril and indaparnide showed renal protection efficiency, expressing in a significant decrease in blood creatinine level and alrnost twofold reduction of MAU level. Perindopril and indaparnide in the rnode of cornbination therapy in patients with rnild and rnoderate arterial hypertension showed rnetabolic neutrality in relation to lipid and carbohydrate metabolism, clinical safety. A side effect as dry cough was observed in one patient only at the end of 12-weeks treatrnent (4.3%). Conclusion. Therefore, our research showed a high antihypertensive efficacy of cornbination therapy with perindopril and indaparnide with the available cardio-, vaso-, and nefroprotection, rnetabolic neutrality and clinical safety that recommends the preparation for the treatrnent of patients with rnild and moderate arterial hypertension.